Infocommunication skills as a rehabilitation and social reintegration tool for inmates - Oliveira, Lídia; Graça, Daniela (Advances in religious and cultural studies, 2019)
"This book explores the existence or lack of infocomunication skills in individuals or groups. It also aims at developing knowledge about the ways to promote digital literacy in prison context, which promote better social integration of inmates facing the end of their sentences"--